Rodents of the subfamily Caviinae (Hystricognathi, caviidae) as hosts for hard ticks (Acari: Ixodidae). - Guglielmone, Alberto Alejandro (2010)
There are only 33 records of rodents of the subfamily Caviinae Fischer de Waldheim, 1817 (Hystricognathi: Caviidae) infested by hard ticks in South America, where the subfamily is established. Caviinae is formed by three genera: Cavia Pallas, 1766, Galea Meyen, 1833 and Microcavia Gervais and Ameghino, 1880. Records of Amblyomma pictum Neumann, 1906, A. dissimile Koch, 1844 and A. pseudoparvum Guglielmone, Keirans and Mangold, 1990 are considered doubtful. Bona fide records are all for localities south of the Amazonian basin in Argentina, Bolivia, Uruguay and Brazil. Thirteen records are for A. tigrinum Koch, 1844, four for A. triste Koch, 1844, three for A. parvum Aragão, 1908 (larvae and nymphs of these three species), one for A. cajennense (Fabricius, 1787) (nymph), four for Ixodes longiscutatus Boero, 1944 (females, nymphs and larvae) and one record for I. loricatus Neumann, 1899 (female). Rodents of the subfamily Caviinae are vital for the life cycle of A. tigrinum and A. parvum and probably for A. triste and I. longiscutatus. It is hypothesized that Ixodidae precedes Caviinae in establishment in South America (Neotropical), therefore this host-relationship is relatively recent measured in evolutionary times starting in late Miocene or afterwards. Rodents of the subfamily Caviinae appears to be relevant for the life cycle and speciation of hard ticks in South America as shown by studies carried out in Argentina and Uruguay. This role has been hidden presumably because this type of hosts was ignored in most ecological tick studies performed in South America.